Natural Management Strategies for Jassids in Agriculture Systems: A Comprehensive Review - Lekhu Gehlot; Neha Parihar; Mukul Gehlot; Kheev Raj (The Bioscan, 2025)
Jassids (Hemiptera: Cicadellidae) are significant agricultural pests that damage various crops, including legumes, cotton,chili, okra, and eggplant, causing substantial yield losses through direct feeding and the transmission of viruses. However, the use of synthetic pesticides in conventional management has resulted in environmental deterioration and health hazards, including the development of insecticide resistance, adverse effects on non-target organisms, pesticide residue contamination, biodiversity loss, and farmer exposure to toxins. This review synthesizes current research on natural management strategies within integrated pest management (IPM) frame works, evaluating their effectiveness, ecological benefits, and alignment with sustainable agriculture. Natural methods emphasize that biological pesticides, such as those derived from neem (e.g., neem seed kernel extract and neem oil), have consistently demonstrated effectiveness in suppressing jassid populations. Additionally, beneficial fungi, such as Beauveria bassiana, Lecanicillium lecanii,and Metarhizium anisopliae, are recognized for their potential in biological control. Moreover, conserving and enhancing populations of natural enemies, such as various predators (e.g., spiders, lacewings, ladybird beetles, and syrphid flies), plays a crucial role in keeping jassid densities below the Economic Threshold Level (ETL), supporting density-dependent regulation. These approaches decrease dependency on chemical pesticides, reduce soil and water contamination, and protect non-target species, including pollinators. This review underscores the urgent need to transition from chemical-intensive practices to sustainable, natural approaches, ensuring agriculture aligns with long-term health and environmental sustainability goals. KEYWORDS Jassids, Natural Management, Botanical Pesticides, Entomopathogens, Biological Control, Natural Enemies, Integrated Pest Management, Sustainable Agriculture